RISK AS A MOTIVATION FOR ADVENTURE TOURIST - Akbar, Muhammad Dhaifan (ITB Journal Publisher, LPPM ITB, 2017)
Adventure activities are commonly associated with risky activities. The affiliation between adventure tourism and risk has made adventure tourism experience distinct from other tourism subset. Therefore risk plays a role as motivation factor for adventure tourists’ to participate in adventure activities. However, different study mentioned that adventure tourist’s unwillingness to be the subject of actual risk also provide a different view on risk role in adventure tourism. This research aims to investigate the role of risk for adventure tourists’ motivation to engage with adventure tourism. This study uses quantitative research methods to achieve its aim. The data was gathered using a self-completion questionnaire, which targeted adventure tourists through the internet. This questionnaire was posted to several adventure-affiliated groups found in social network for foreseeable time and able to get reasonable amount of responds from intended target. The findings confirm that risk affiliation with adventure tourism activities exists through tourism perspective. The findings also confirm that risk is part of tourists’ motivation to take part in adventure, hence describe role of risk in adventure activities